Reply to comment by Takahashi T on: Prostate cancer screening in Switzerland: a literature review and consensus statement from the Swiss Society of Urology - Christoph Würnschimmel; Dominik Menges; Maciej Kwiatkowski; Silvan Sigg; Lukas Prause; Agostino Mattei; Daniel Engeler; Daniel Eberli; Helge Seifert; Massimo Valerio; Cyrill A. Rentsch; Ashkan Mortezavi (Swiss Medical Weekly)
No abstract available.